The hidden curriculum and its role in curriculum innovation implementation - Matorevhu, Alois; Madzamba, Havatidi (Univeritas Papua, 2022)
The hidden curriculum comprises unspoken or implicit values, behaviors, procedures, and norms in an educational setting. This can be an alternative to empowering attitudes, values, ​​and non-cognitive skills, for example, politeness, honesty, hard work, cooperation, and tolerance in students during the implementation of curriculum innovations.. An alignment between the intended/official curriculum innovation implementation and the implemented curriculum innovation encourages the positive manifestation of the hidden curriculum. Negative manifestation of the hidden curriculum due to misalignment between intended/official curriculum innovation implementation and the implemented curriculum innovation makes the envisaged change through curriculum innovation implementation elusive, like a mirage that can never be caught. This paper critically discusses how the hidden curriculum may promote or hinder successful curriculum innovation implementation. Implications of the hidden curriculum to curriculum innovation implementation are also discussed.